Sirt1-Mediated Anti-Aging Effects of Houttuynia cordata Extract in a High Glucose-Induced Endothelial Cell-Aging Model - Kim, Gi Dae (Preventive nutrition and food science, 2020)
(HC) is a herb widely used in traditional Asian medicine as an ingredient in complex prescriptions. HC is known for its anti-leukemic, anti-oxidative, and anti-inflammatory properties. However, its anti-vascular endothelial aging efficacy and the underlying mechanisms are not fully understood. In this study, we investigated the anti-aging effects of HC in a high glucose (HG)-induced endothelial cell (EC)-aging model. Treatment with HC (40 μg/mL) increased migration of ECs, and increased phosphorylation of extracellular signal-regulated kinases and p38 in a dose-dependent manner. Following HG treatment (30 mM), HC significantly decreased the number of senescence-associated β-galactosidase positive cells, which are the biomarkers for aging, in a dose-dependent manner. Based on levels of phosphorylation, HC (40 μg/mL) was shown to increase expression of sirtuin1 (Sirt1) and endothelial nitric oxide synthase (eNOS) by 74.4% and 328.2%, respectively. Furthermore, treatment of HG-induced senescent ECs with HC (40 μg/mL) significantly increased nitric oxide production ( <0.05). These results demonstrate that HC both increases EC migration and regulates the Sirt1/eNOS pathway, suggesting HC has potential for protecting ECs against HG-induced aging.